Features of using the situational method for training police officers in the use of combat techniques - Troyan E.I.; Shestakova S.V. (Theory and Practice of Physical Culture, 2025)
Introduction. In accordance with the provisions of the "Procedure for organizing the training of personnel to fill positions in the internal affairs bodies of the Russian Federation", the need for training employees of internal affairs bodies in the tactics of using combat techniques in situations of official activity has been determined [1]. In this regard, there was a need to search for and theoretically substantiate the possibility of using the situational method in the physical training of police officers. Purpose of the research – identifying the possibilities and features of using the situational method for training police officers in the use of combat fighting techniques. Research methodology and organization. The study will be conducted from 2020 to 2024 at the Tyumen Institute for Advanced Training of the Ministry of Internal Affairs of the Russian Federation. The study used scientific methods: analysis and generalization of scientific and educational literature, abstraction, modeling of educational situations. Results and its discussion. At different stages of the research, the following were developed: a sensorimotor method, a situationally integrated methodology for teaching combat fighting techniques [2]. The features of using the situational method for training police officers in the use of physical force are: 1. The preparation of a training situation of the use of physical force by police officers includes three stages: the design stage, the technological stage and the reflection stage. 2. Educational situations are examined in comprehensive classes, with the participation of teachers of physical, tactical and legal training disciplines. 2. The training situations are structured according to levels of difficulty with increasing levels of confusing factors that complicate the actions of police officers. 3. The bank of situations is constantly replenished and updated. Conclusion. The results of the study revealed the effectiveness of training police officers in the situational use of combat techniques. The prospect for further self-development of the system of physical training of police officers will be the design and use of various variable situations of the use of physical force.